Aortic Aneurysm as a Complication of Granulomatosis with Polyangiitis Successfully Treated with Prednisolone and Cyclophosphamide: A Case Report and Review of the Literature - Naoko Niimi; Tomoko Miyashita; Kana Tanji; Takuya Hirai; Kozo Watanabe; Keigo Ikeda; Shinji Morimoto; Iwao Sekigawa (Case Reports in Rheumatology)
A 57-year-old Japanese man was admitted to the hospital with back pain and fever, multiple lung nodules, and abdominal aortic aneurysm (AAA). Laboratory tests performed at admission showed an increased proteinase 3 anti-neutrophil cytoplasmic antibody (PR3-ANCA) level. Video-associated thoracoscopic lung biopsy was performed; pathologic examination showed granulation tissue with necrosis and multinucleated giant cells. The diagnosis of granulomatosis with polyangiitis (GPA) was confirmed on the basis of the clinical presentation, laboratory findings, and lung biopsy. All symptoms were ameliorated, and the serum level of PR3-ANCA declined following treatment with prednisolone and cyclophosphamide. Although the association of GPA with AAA is rare, GPA may be included among the large vessel vasculitides that can give rise to aortic aneurysm.